Shocking interest rate floors - Fabio Canetg; Daniel Kaufmann (University of Bern, Department of Economics, 2019)
We identify the dynamic causal effects of interest rate floor shocks, exploiting regular auctions of Swiss central bank debt securities (SNB Bills). A theoretical model shows that variation in the volume of, and yield on, central bank debt changes the interest rate floor. In addition, the model establishes the equivalence between central bank debt and interest-bearing reserves when reserves are ample. Based on these insights, the empirical analysis identifies an interest rate floor shock in a dynamic event study of SNB Bill auctions. A restrictive interest rate floor shock causes an increase in the money market rate, a persistent appreciation of the Swiss franc, a decline in long-term interest rates, and a decline in stock prices. We then perform policy experiments under various identifying assumptions in which the central bank raises the interest rate floor from 0% to 0.25%. Such a policy change causes a 3-6% appreciation of the Swiss franc and a 5-20% decline in stock prices.
Keywords: E41; E43; E44; E52; E58; C32; 330; Exit strategies; interest rate floors; central bank debt securities; interest on reserves; monetary policy shocks; identification through heteroscedasticity